Ethics of AIDS research in a developing country: balacing power in disguise - M.B., M.W. Makgoba (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Chairperson, Honourable Ministers of Health, distinguished colleagues, ladies and gentlemen. It is indeed a great honour for me and the organisation I represent, the MRC, to be given an opportunity to share some thoughts and experiences on the issue of "Ethics of Aids Research in Developing Countries on this prestigious plenary. I thank the organisers of the 13’" International Aids Conference for this opportunity. For the purpose of this talk, I have modified the title to "Ethics of Aids Research in a Developing Country - Balancing Power in Disguise".